Water-soluble flux for solder paste and solder paste

The water-soluble flux with specific components and ratios addresses the drying issue of solder pastes, maintaining adhesion and enabling water-based cleaning, thus improving bonding reliability and environmental safety.

JP7663006B2Active Publication Date: 2025-04-16MITSUBISHI MATERIALS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021049821
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-04-16
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

Existing solder pastes using low-heat-resistant fluxes dry out quickly when left for a long time, leading to adhesion issues with electronic components.

Method used

A water-soluble flux comprising organic acid polyglycerol ester, solvent, thixo agent, and surfactant, with specific mass ratios, that improves heat resistance and prevents drying of the solder paste surface.

Benefits of technology

The flux maintains adhesion to chips or substrates even after prolonged exposure, ensuring reliable bonding and allowing for water-based reflow cleaning, enhancing safety and environmental sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663006000001
    Figure 0007663006000001
  • Figure 0007663006000002
    Figure 0007663006000002
  • Figure 0007663006000003
    Figure 0007663006000003
Patent Text Reader

Abstract

To provide a water soluble flux for preparing a solder paste which hardly dries even when being left in the ambient air for a long term, and a solder paste.SOLUTION: A water soluble flux for a solder paste comprises: an organic acid polyglycerol ester which is a caprylic acid polyglycerol ester and the like; a solvent which is a tetraethylene glycol and the like; a thixotropic agent which is benzylidene sorbitol and the like; and a surfactant which is a bis(2-hydroxyethyl) lauryl amine and the like. The water soluble flux for the solder paste includes 40-60 mass% of organic acid polyglycerol ester, 20-35 mass% of the solvent, 5-10 mass% of the thixotropic agent, and 10-25 mass% of the surfactant when the content of the water soluble flux is 100 mass%. Steam pressure of the water soluble flux for the solder paste at 20°C is 10 Pa or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-soluble flux used in a solder paste for joining metals together, and to a solder paste prepared using this flux. [Background technology]

[0002] In general, when mounting electronic components such as chip components on a printed circuit board, it is known that solder paste is printed on the surface of the printed circuit board using a printing mask, the electronic components are mounted on the printed solder paste portion, and then the solder paste is melted and solidified by reflow to mount the electronic components.

[0003] In the above mounting method of electronic components, there are cases where the solder paste must be left for a long time after printing due to the design of the production line. In such cases, the solder paste using a flux with low heat resistance, such as a low melting point paste containing Sn-Ag-Cu system (Sn 96.5 mass%, Ag 3.0 mass%, Cu 0.5 mass%) solder powder with a eutectic temperature of 217°C, dries out the paste surface, and when mounting electronic components, even if you try to fix the electronic components on the paste by using the adhesiveness of the solder paste, it becomes impossible to fix them because the paste surface is dry.

[0004] In order to solve these problems, a method for shaping a solder shape has been disclosed in which the surface of a printed circuit board on which cream solder (solder paste) has been printed faces downwards, and the printed circuit board is shaped while being subjected to vibration during shaping (see, for example, Patent Document 1 (Claim 1, Claim 2, Paragraphs

[0001] to

[0003] , Paragraph

[0036] , Paragraph

[0037] )).

[0005] Patent Document 1 describes that according to this shaping method, by turning the surface of the printed circuit board on which the cream solder is printed downward, the cream solder is caused to sag vertically and the solder shape is shaped to increase the distance between the cream solder, thereby making it possible to prevent short circuits between circuit patterns and an increase in solder balls. It also describes that by applying vibration to the printed circuit board with the cream solder printed surface facing downward, it becomes possible to promote sagging in the vertical direction and shape the solder.

[0006] On the other hand, the present applicant has proposed a flux containing an organic acid polyglycerol ester, a solvent, an activator, a thixotropic agent, and an antioxidant as a water-soluble flux for solder paste (see Patent Document 2 (Claim 1, paragraph

[0016] )). This flux is characterized in that the solvent contains one or more organic solvents having two or more hydroxyl groups in one molecule, a boiling point of 200 to 400°C, and a melting point of less than 25°C, the activator is a nonionic organic halogen compound and / or an organic compound having two or more hydroxyl groups in one molecule and a melting point of 25°C or higher, and when the total amount of the water-soluble flux for solder paste is taken as 100% by mass, the content of the organic acid polyglycerol ester is 10% by mass or more and less than 50% by mass, the content of the solvent is 30 to 60% by mass, the content of the activator is 0.1 to 20% by mass, the content of the thixotropic agent is 1 to 10% by mass, and the content of the antioxidant is 1 to 10% by mass.

[0007] The water-soluble flux for solder paste shown in Patent Document 2 can impart excellent printability and melting properties to the solder paste during mounting, and even when used as a flux for high-temperature soldering, it can be washed with water only after reflow without using organic solvents, etc., and has the effect of preparing a solder paste that is excellent in terms of safety, hygiene, and the environment during mounting. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2000-196233 A [Patent Document 2] Patent No. 6668664 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the method of shaping the solder shape shown in Patent Document 1 requires an inversion device for turning the surface of the printed circuit board on which the cream solder is printed downward, and a vibration device for applying vibration to the printed circuit board, which makes the mounting equipment complicated.In addition, if the cream solder is left in the air for a long time after printing, the cream solder dries out, regardless of whether the printed surface is turned downward or whether vibration is applied with the printed surface turned downward, resulting in poor adhesion to the chip and circuit board.

[0010] In addition, although the water-soluble flux for solder paste disclosed in Patent Document 2 has the above-mentioned excellent effects, when it is prepared into a solder paste, printed, and then left in the air for a long period of time, there arises the same problem as the invention of Patent Document 1.

[0011] An object of the present invention is to provide a water-soluble flux and a solder paste for preparing a solder paste that does not easily dry even when left in the air for a long period of time.

[0012] A first aspect of the present invention is a water-soluble flux for solder paste, comprising an organic acid polyglycerol ester, a solvent, a thixotropic agent, and a surfactant, the surfactant being one or more selected from the group consisting of nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants, the organic acid polyglycerol ester being one or more selected from the group consisting of polyglycerol laurate, polyglycerol stearate, polyglycerol isostearate, polyglycerol sesquistearate, polyglycerol diisostearate, polyglycerol myristic acid, polyglycerol palmitate, polyglycerol oleate, behenic acid The water-soluble flux is characterized in that the water-soluble flux is one or more selected from the group consisting of polyglycerol esters, and caprylic acid polyglycerol esters, the solvent is one or more selected from the group consisting of triethylene glycol monomethyl ether, terpene alcohol, diethylene glycol monobutyl ether, diglycerin, and tetraethylene glycol, the thixotropic agent is benzylidene sorbitol and / or hydrogenated castor oil, and contains 40% by mass to 60% by mass of organic acid polyglycerol ester, 20% by mass to 35% by mass of solvent, 5% by mass to 10% by mass of thixotropic agent, and 10% by mass to 25% by mass of surfactant, when the water-soluble flux is taken as 100% by mass, and has a vapor pressure of 10 Pa or less at 20°C.

[0013] A second aspect of the present invention is an invention based on the first aspect, characterized in that the water-soluble flux for solder paste further contains an activator, the activator being one or more selected from the group consisting of caprylic acid, pelargonic acid, and lactic acid, and the activator is contained in an amount of 3% by mass to 10% by mass when the water-soluble flux is taken as 100% by mass.

[0014] A third aspect of the present invention is a solder paste comprising the water-soluble flux for solder paste according to the first or second aspect and solder powder. Effect of the Invention

[0015] In the water-soluble flux for solder paste according to the first aspect of the present invention, the components constituting the flux, that is, the organic acid polyglycerol ester, the solvent, the thixotropic agent and the surfactant, are each selected as predetermined components and each component is contained in a predetermined ratio. Therefore, even when a paste prepared using this flux is printed and then left in the air for a long period of time, the heat resistance of the flux is enhanced, the surface of the paste hardly dries out and adhesion to the chip or board can be maintained.

[0016] The water soluble flux for solder paste according to the second aspect of the present invention further contains an activator. By setting the content of the activator to 3% by mass to 10% by mass, the solder powder melts quickly, sufficient bonding strength is obtained, and reaction of the activator with the solder powder during storage is suppressed, thereby ensuring the storage stability of the solder paste.

[0017] In the solder paste of the third aspect of the present invention, even when a paste prepared using the flux of the first or second aspect is printed and then left in the air for a long period of time, the heat resistance of the flux is enhanced, the surface of the paste hardly dries out, and adhesion to the chip or board is maintained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Next, an embodiment for carrying out the present invention will be described. The water-soluble flux for solder paste of the present invention includes an organic acid polyglycerol ester, a solvent, a thixotropic agent, and a surfactant. The surfactant is one or more selected from the group consisting of nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants. The organic acid polyglycerol ester is obtained by esterification reaction of polyglycerin obtained by dehydration condensation of glycerin with an organic acid. Specifically, the organic acid polyglycerol ester is one or more selected from the group consisting of polyglycerol laurate, polyglycerol stearate, polyglycerol isostearate, polyglycerol sesquistearate, polyglycerol diisostearate, polyglycerol myristic acid, polyglycerol palmitate, polyglycerol oleate, polyglycerol behenate, and polyglycerol caprylate. The organic acid polyglycerol ester described above has an advantage that the molecular weight of the monomer is smaller than that of other organic acid polyglycerol esters, and therefore it is easily removable after reflow.

[0019] The solvent is one or more selected from the group consisting of triethylene glycol monomethyl ether, terpene alcohol, diethylene glycol monobutyl ether, diglycerin, and tetraethylene glycol. The above-mentioned solvents have the features of a lower vapor pressure and a higher drying resistance than other solvents.

[0020] The thixotropic agent is benzylidene sorbitol (1,3:2,4-bis-O-(benzylidene) sorbitol) and / or hydrogenated castor oil. The above-mentioned thixotropic agent has the advantage that it is easier to impart thixotropy due to intermolecular hydrogen bonds compared to other thixotropic agents.

[0021] Examples of the nonionic surfactant include ether-type nonionic surfactants such as polyoxyalkylene alkyl ethers such as polyoxyethylene lauryl ether, polyalkylene glycols, polyoxyalkylene alkenyl ethers, and polyoxyalkylene derivatives; (2-hydroxyethyl) alkylamines such as bis(2-hydroxyethyl) laurylamine, alcohol amines such as triethanol, polyoxyethylene alkylamines, N,N',N'-tris(2-hydroxyethyl)-N-alkyl-1,3-diaminoalkanes, N,N',N'-polyoxyethylene-N-alkyl-1,3-diaminoalkanes, polyoxypropylene glycol ... Examples of nonionic surfactants include alkylamine ether type nonionic surfactants such as polyoxyethylene alkylamines; ester type nonionic surfactants such as fatty acid esters, glycol fatty acid esters, and sorbitan fatty acid esters; ether ester type nonionic surfactants such as polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, glycerin fatty acid esters, polyoxyethylene fatty acid esters, polyoxyethylene hydrogenated castor oil, and alkyl alkanolamides; and amino acid derivative type nonionic surfactants such as N-acyl amino acid esters, N-acyl glutamic acid esters, and pyroglutamic acid esters. Other examples of nonionic surfactants include phenol ethoxylates, silicone surfactants, and fluorine-based surfactants. Examples of the cationic surfactant include surfactants such as alkylamine salts, for example, quaternary ammonium salts, such as lauryltrimethylammonium chloride. Examples of the anionic surfactant include polyoxyethylene alkyl ether sulfate salts such as sodium polyoxyethylene lauryl ether sulfate, aliphatic phosphate esters such as aromatic phosphate esters, sodium dioctyl sulfosuccinate, sodium alcohol sulfate, alkyl sulfate ester salts, alkylbenzene sulfonate salts, fatty acid salts, and naphthalenesulfonate-formaldehyde condensates. Further, examples of the amphoteric surfactant include alkyl betaines such as lauryl betaine, fatty acid amido alkyl acetic acid betaines, fatty acid amino acetic acid betaines, and alkyl amine oxides. The above-mentioned surfactants have the advantages of having a lower vapor pressure and a higher drying resistance than other surfactants.

[0022] When the water-soluble flux is taken as 100 mass%, the content of the organic acid polyglycerol ester is 40 mass% to 60 mass%, preferably 44 mass% to 55 mass%. The content of the solvent is 20 mass% to 35 mass%, preferably 27 mass% to 34 mass%. The content of the thixotropic agent is 5 mass% to 10 mass%, preferably 2.2 mass% to 7 mass%. The content of the surfactant is 10 mass% to 25 mass%, preferably 10 mass% to 20 mass%. Furthermore, the flux has a vapor pressure of 10 Pa or less, preferably 1 Pa or less at 20°C. This vapor pressure is measured by the Knudsen effusion method using a vapor pressure measuring device VPR (manufactured by Japan Science Core Co., Ltd.).

[0023] If the content of the organic acid polyglycerol ester is less than the lower limit, the fluidity of the paste and the tacking property to the substrate are reduced, and thus the bumps after printing may have defects such as defective shape. On the other hand, if the content exceeds the upper limit, the viscosity of the flux becomes too high, and the viscosity of the paste also becomes high accordingly, which may cause defects such as defective shape of the bumps after printing, or defects such as missing, in which the paste is not discharged from the mask opening and the bumps are not formed. Also, if the content of the solvent is less than the lower limit, the viscosity of the flux becomes high, and the viscosity of the paste becomes too high accordingly, which may cause defects such as defective shape of the bumps and missing. On the other hand, if the content exceeds the upper limit, the viscosity of the flux becomes low, and the viscosity of the paste also becomes too low accordingly, which may cause defects such as the solder powder in the paste settling and separating out.

[0024] In addition, if the content of the thixotropic agent is less than the lower limit, the shape retention of the solder paste is reduced, and adjacent bumps may be connected to each other, resulting in defects such as so-called bridging. On the other hand, if the content exceeds the upper limit, the viscosity of the flux increases, and the paste viscosity becomes too high accordingly, which may result in defects such as the above-mentioned defective shape of the bumps and missing bumps. In addition, if the content of the surfactant is less than the lower limit, when a large number of solder bumps are formed on a substrate, the paste becomes difficult to flow when made into a solder paste, and missing bumps occur, in which no bumps are formed. On the other hand, if the content exceeds the upper limit, the paste becomes easy to flow when made into a solder paste, and adjacent bumps may be connected to each other, resulting in so-called bridging. Furthermore, if the vapor pressure of the flux exceeds the upper limit, when the solder paste containing this flux is applied to a substrate and left for a long time (for example, a time significantly longer than 2 hours) until a semiconductor chip is mounted, the surface of the applied paste dries, making it impossible to bond without pressure.

[0025] The flux may contain an activator, an antioxidant, etc., in addition to the organic acid polyglycerol ester, the solvent, the thixotropic agent, and the surfactant. The activator is one or more selected from the group consisting of caprylic acid, pelargonic acid, and lactic acid. The antioxidant may be a phenol-based antioxidant, a phosphorus-based antioxidant, a sulfur-based antioxidant, or an amine-based antioxidant. When the water-soluble flux is 100% by mass, the content of the activator is preferably 3% to 10% by mass, and more preferably 4% to 7% by mass. The content of the antioxidant is preferably 1% to 2% by mass. If the preferred content of the activator is less than the lower limit, the solder powder may not melt and sufficient bonding strength may not be obtained. On the other hand, if the content exceeds the upper limit, the activator may easily react with the solder powder during storage, which may reduce the storage stability of the solder paste. Furthermore, if the preferred content of the antioxidant is less than the lower limit, the solder powder and the flux component are more likely to react with each other, which may reduce the storage stability of the solder paste, whereas if the content exceeds the upper limit, the melting property of the solder powder may decrease.

[0026] To prepare a solder paste using the flux thus obtained, the flux and solder powder are mixed in a desired ratio. The solder powder to be used is not particularly limited, and general solder powders mainly composed of tin can be used. For example, Sn-Pb solder (composition Sn:Pb=63:37 mass %, etc.), Sn-Pb-Ag solder (composition Sn:Pb:Ag=62:36:2 mass %, etc.), Sn-Pb-Bi solder (composition Sn:Pb:Bi=57:40:3 mass %, etc.), Sn-Pb-Sb solder (composition Sn:Pb:Sb=8:86:6 mass %, etc.), Sn-Ag solder (composition Sn:Ag=97.7:2.3% by mass, etc.), Sn-Cu solder (composition Sn:Cu=98.3:0.7% by mass, etc.), Sn-Ag-Cu solder (composition Sn:Ag:Cu=96.5:3:0.5% by mass, etc.), Au-Sn high-temperature solder (composition Au:Sn=75-85:25-15% by mass, and composition Au:Sn=5-15:95-85% by mass, etc.), %, especially composition Au:Sn=78-80:22-20% by mass and composition Au:Sn=10:90% by mass, etc.), Au-Si based high temperature solder (composition Au:Si=81.4:18.6% by mass, etc.), Au-Ge based high temperature solder (composition Au:Ge=92.6:7.4% by mass, etc.), Sn-Pb based high temperature solder (composition Sn:Pb=5:95% by mass, etc.), In addition, examples of the solder powder include Zn-Sn solder (composition Zn:Sn=9:91 mass %), In-Sn solder (composition In:Sn=52:48 mass %), Bi-Sn solder (composition Bi:Sn=58:42 mass %), Sb-Sn solder (composition Sb:Sn=5:95 mass %), and Al-Zn solder (composition Al:Zn=5:95 mass %). The average particle size of the solder powder is not particularly limited as long as it is within the range used in general solder pastes, but for example, a solder powder in the range of 0.1 μm to 1 mm can be suitably used. In consideration of narrow pitch printing, the average particle size of the solder powder is preferably within the range of 0.1 μm to 50 μm, and more preferably within the range of 1 μm to 20 μm when considering fine bump formation. In this specification, the average particle size is the volume-based average particle size D measured using a laser diffraction scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., model name: Partica LA-950). 50 This refers to.

[0027] The amount of flux mixed in preparing the solder paste is preferably adjusted so that the proportion of flux is 3% to 60% by mass when the prepared paste is taken as 100% by mass. If the amount of flux is less than the lower limit, the amount of flux is small, which may make it difficult to make a paste, or may cause problems such as the solder powder not melting. On the other hand, if the amount of solder powder contained in the paste is small, the amount of solder powder contained in the paste may be small, and the required amount of solder may not be obtained after melting.

[0028] In the solder paste prepared in this way, the components constituting the flux, such as organic acid polyglycerol ester, solvent, thixotropic agent, and surfactant, are selected as specific components, and the ratios of each component are set to specific values. Even if the paste prepared using this flux is left in the air for a long time after printing, the heat resistance of the flux is increased, the surface of the paste hardly dries, and the adhesion to the chip and the board can be maintained. In addition, while maintaining good printability or meltability suitable for bump formation and narrow pitch printing, cleaning after reflow can be performed with only water, and it is excellent in terms of safety, hygiene, and the environment during mounting. Therefore, this solder paste can be used preferably in mounting technologies such as FC bonding technology. EXAMPLES

[0029] Next, examples of the present invention will be described in detail together with comparative examples.

[0030] <Examples 1 to 24 and Comparative Examples 1 to 12> An organic acid polyglycerol ester, a solvent, an activator, a thixotropic agent, and a surfactant were prepared. These were mixed in the ratios shown in Tables 2 and 3 below, and then mixed and stirred to obtain a flux. In Tables 2 and 3, the organic acid polyglycerol esters shown in Classes A to H, the solvents shown in Classes A to F, the activators shown in Classes A to E, and the thixotropic agents shown in Classes A and B are shown in Table 1. In Table 1, the surfactants shown in Classes A to D are polyoxyethylene lauryl ether (Class A), which is an ether-type nonionic surfactant, bis(2-hydroxyethyl)laurylamine (Class B), which is also an ether-type nonionic surfactant, sodium polyoxyethylene lauryl ether sulfate (Class C), which is an anionic surfactant, and lauryl trimethylammonium chloride (Class D), which is a cationic surfactant. In Table 1, the number written at the end of the name of the organic acid polyglycerol ester indicates the polymerization number of polyglycerol.

[0031] [Table 1]

[0032] [Table 2]

[0033] [Table 3]

[0034] <Comparative Test> The following evaluations (i) to (iv) were carried out using the fluxes obtained in Examples 1 to 24 and Comparative Examples 1 to 12. The vapor pressure of the fluxes at 20°C was also measured by the method described above. These results are shown in Tables 4 and 5. Tables 4 and 5 also show the two types of solder powders used.

[0035] (i) Drying resistance of solder paste: Two types of solder paste were prepared from two types of solder powder. First, Sn-Ag-Cu solder powder (composition: Sn 96.5 mass%, Ag 3.0 mass%, Cu 0.5 mass%) with an average particle size of 8 μm was prepared, and 89.0 parts by mass of this solder powder and 11.0 parts by mass of the flux obtained in each of Examples 1 to 11, 13 to 24 and Comparative Examples 1 to 12 were stirred and mixed at room temperature to prepare a solder paste. In Tables 4 and 5, this solder powder is described as "SAC305". Next, an Au-Sn solder powder (composition: Au 78.0 mass%, Sn 22.0 mass%) with an average particle size of 8 μm was prepared, and 94.0 parts by mass of this solder powder and 6.0 parts by mass of the flux obtained in Example 12 were stirred and mixed at room temperature to prepare a solder paste. In Table 4, this solder powder is described as "Au22Sn." The average particle size of the solder powder was measured using a laser diffraction scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., model name: Partica LA-950) to determine the volume-based average particle size D 50 It is. The drying resistance of the solder paste was judged by the following method. That is, the prepared solder paste was printed on a flat Kovar substrate with Au metallization using a stencil mask (mask opening size 1 mm square, mask thickness 50 μm). After storing it for 8 hours in a windless environment in a clean room controlled at a temperature of 24°C and humidity of 50%, a dummy Si chip (length 1 mm × width 1 mm × thickness 0.3 mm) with Au metallization was mounted on it, and the substrate was slowly turned over to judge whether the chip fell off the paste or not to judge whether the paste surface was dry or not. If the chip did not fall off the paste when turned over, it was judged as "good", and if it fell off, it was judged as "bad".

[0036] (ii) Bump printability (substrate): The above-mentioned solder paste was printed on a silicon substrate (dimensions: length 60 mm × width 60 mm × thickness 0.8 mm) using a small semi-automatic screen printer equipped with a Ni-plated metal mask plate (outer dimensions: length 300 mm × width 3000 mm × thickness 20 μm, aperture diameter φ: 75 μm, aperture pitch: 100 μm) with multiple openings, to form solder bumps on the substrate. The substrate was equipped with a copper foil with a thickness of about 50 μm provided on one side of the substrate, and a resist film (film thickness 15 μm, aperture diameter φ65 μm, aperture pitch 100 μm) provided on the copper foil and with multiple openings formed thereon that penetrate to the copper foil. Among 20,000 solder bumps formed on the substrate, the number of missing bumps where no bumps were formed and the number of bridges connecting adjacent bumps were counted. A test piece with five or fewer missing bumps and bridges was rated "good," and a test piece with six or more missing bumps and bridges was rated "poor."

[0037] (iii) Bump melting property (substrate): The substrate on which the solder bumps were formed in the above-mentioned bump printability test was melted under the following conditions using a reflow furnace (manufactured by Malcom, model name: SRS-1C). For the solder bumps formed by the solder paste using the Sn-Ag-Cu solder powder in Examples 1 to 11, 13 to 24 and Comparative Examples 1 to 12, the substrate was heated in a nitrogen atmosphere from room temperature to 150°C at a heating rate of 1.5°C / s, pre-dried at 150°C for 2 minutes, and then heated from 150°C to 230°C at a heating rate of 1.5°C / s, and heated at 230°C for 5 seconds to melt the solder bumps on the substrate. For the solder bumps formed with the solder paste using the Au-Sn solder powder of Example 12, the temperature was increased from room temperature to 220°C at a rate of 1.5°C / s, pre-dried at 220°C for 2 minutes, and then increased from 220°C to 300°C at a rate of 1.5°C / s, and heated at 300°C for 5 seconds to melt the solder bumps on the board. The appearance after reflow was visually observed, and the case where no uncohesive solder was found around the bumps was rated as "good", and the case where uncohesive solder was found was rated as "poor".

[0038] (iv) Flux cleaning property (substrate): 50 ml of ion-exchanged water in a 100 ml glass beaker was heated to 60°C using a hot plate. The substrate after the above-mentioned melting test was placed in the beaker containing the 60°C ion-exchanged water, and the beaker was placed in an ultrasonic cleaner and subjected to ultrasonic waves for 5 minutes. The substrate was then removed from the beaker, the water was removed using an air blower, and the substrate was dried at 50°C for 5 minutes using a dryer. The bump portion after reflow and cleaning was observed using a backscattered electron image of a scanning electron microscope (SEM: manufactured by JEOL Ltd., model name: JSM-6510LV) to confirm the presence or absence of organic component residues. Based on the presence or absence or the degree of organic component residues at this time, the case where there was almost no residue or the residue was confirmed to be less than 5% of 100% of the bump surface area was judged to be "good", and the case where the residue was confirmed to be 5% or more of 100% of the bump surface area was judged to be "poor".

[0039] [Table 4]

[0040] [Table 5]

[0041] <Evaluation> As is clear from Tables 3 and 5, in Comparative Example 1, the content of organic acid polyglycerol ester was 38 mass%, which was below the aforementioned range, so the fluidity of the solder paste and its tackiness to the board were reduced, and the bump printability was "poor."

[0042] In Comparative Example 2, the solvent content was 17 mass %, which was below the aforementioned range, so the viscosity of the flux increased, and the viscosity of the solder paste became too high, resulting in both the bump printability and bump meltability being "poor."

[0043] In Comparative Example 3, the solvent content was 50 mass%, which exceeded the aforementioned range, so the viscosity of the flux was low, and the viscosity of the solder paste was too low, resulting in both the bump printability and bump meltability being "poor."

[0044] In Comparative Example 4, diethylene glycol monobutyl ether acetate (class F), which is not a specified solvent and has a high vapor pressure, was used as the solvent, so the vapor pressure of the flux at 20°C was 67 Pa and the drying resistance of the solder paste was "poor."

[0045] In Comparative Example 5, the content of the thixotropic agent was 0.5 mass %, which was below the aforementioned range, so the shape retention of the solder paste was reduced, and the bump printability was "poor."

[0046] In Comparative Example 6, the content of the thixotropic agent was 15 mass %, which exceeded the above-mentioned range, and therefore the viscosity of the flux increased, and the viscosity of the solder paste became too high, resulting in a "poor" flux cleanability.

[0047] In Comparative Example 7, the surfactant content was 3 mass%, which was below the aforementioned range, so when flux was used to make a solder paste, the paste did not flow easily, resulting in missing bumps and bridges, and the bump printability was "poor."

[0048] In Comparative Example 8, lauryltrimethylammonium chloride (Class D), which is not a specified surfactant and has a high vapor pressure, was used as the surfactant, and therefore both the drying resistance and bump printability of the solder paste were "poor."

[0049] In Comparative Example 9, butyric acid (Class D), which has a high vapor pressure, was used as the activator instead of the specified activator. As a result, the vapor pressure of the flux at 20°C increased significantly to 227 Pa, and both the drying resistance of the solder paste and the bump melting property were "poor."

[0050] In Comparative Example 10, valeric acid (class E), which has a high vapor pressure, was used as the activator instead of the specified activator, so the vapor pressure of the flux at 20°C was 26 Pa, and both the drying resistance and bump melting properties of the solder paste were ``poor.''

[0051] In Comparative Example 11, the content of organic acid polyglycerol ester was 70 mass %, which exceeded the aforementioned range, so the viscosity of the flux increased, the viscosity of the solder paste became too high, and the bump printability was "poor."

[0052] In Comparative Example 12, the surfactant content was 30 mass%, which exceeded the aforementioned range. Therefore, when the flux was used to make a solder paste, the paste was prone to flow, adjacent bumps were connected to each other, and the bump printability was "poor."

[0053] In contrast, as is clear from Tables 2 and 4, in Examples 1 to 24, the components constituting the flux, that is, organic acid polyglycerol ester, solvent, thixotropic agent, and surfactant, were selected as specified components, and each component was contained in a specified ratio, so that the vapor pressure of the flux at 20°C was 10 Pa or less, and the drying resistance, bump printability, bump meltability, and flux cleanability of the solder paste were all "good."

[0054] The water-soluble flux for solder paste of the present invention can be widely used for mounting electronic components (particularly mounting techniques that require bump formation, narrow-pitch printing, etc., such as FC bonding technology) and bonding other components.

Claims

1. The composition includes an organic acid polyglycerol ester, a solvent, a thixotropic agent, and a surfactant, The water-soluble flux for solder paste is characterized in that the surfactant is one or more selected from the group consisting of nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants, the organic acid polyglycerol ester is one or more selected from the group consisting of polyglycerol laurate, polyglycerol stearate, polyglycerol isostearate, polyglycerol sesquistearate, polyglycerol diisostearate, polyglycerol myristic acid, polyglycerol palmitate, polyglycerol oleate, polyglycerol behenate, and polyglycerol caprylate; the solvent is one or more selected from the group consisting of triethylene glycol monomethyl ether, terpene alcohol, diethylene glycol monobutyl ether, diglycerin, and tetraethylene glycol; the thixotropic agent is benzylidene sorbitol and / or hydrogenated castor oil; When the water-soluble flux is taken as 100 mass %, the water-soluble flux contains 40 mass % to 60 mass % of the organic acid polyglycerol ester, 20 mass % to 35 mass % of the solvent, 5 mass % to 10 mass % of the thixotropic agent, and 10 mass % to 25 mass % of the surfactant, A water-soluble flux for solder paste, characterized in that the vapor pressure at 20°C is 10 Pa or less.

2. The water-soluble flux for solder paste according to claim 1, further comprising an activator, the activator being one or more selected from the group consisting of caprylic acid, pelargonic acid and lactic acid, and the water-soluble flux contains 3% by mass to 10% by mass of the activator when the water-soluble flux is taken as 100% by mass.

3. 3. A solder paste comprising the water-soluble flux for solder paste according to claim 1 or 2 and solder powder.

Citation Information

Patent Citations

  • Water-soluble soldering flux compound for hot air levelling

    CN111730243A

  • Method and device for shaping soldering form of cream solder printed on printed board and method and device for storing printed board printed with cream solder

    JP2000196233A

  • Water-soluble flux for solder paste, and solder paste

    JP2016043397A

  • Water-soluble flux for solder paste, and solder paste

    JP2016043398A

  • Water-soluble flux for solder paste and solder paste

    JP2017064777A